Quality of Life Outcomes for Patients Who Underwent Conventional Resection and Liver Transplantation for Locally Advanced Hepatoblastoma - Zishaan Farooqui; Michael Johnston; Emily Schepers; Nathalie Brewer; Stephen Hartman; Todd Jenkins; Alexander Bondoc; Ahna Pai; James Geller; Gregory M. Tiao (MDPI AG, 2023)
Hepatoblastoma is the most common malignant liver tumor of childhood, with liver transplant and extended resection used as surgical treatments for locally advanced tumors. Although each approach has well-described post-operative complications, quality-of-life outcomes have not been described following the two interventions. Long-term pediatric survivors of hepatoblastoma who underwent conventional liver resection or liver transplantation at a single institution from January 2000-December 2013 were recruited to complete quality-of-life surveys. Survey responses for the Pediatric Quality of Life Generic Core 4.0 (PedsQL, n = 30 patient and n = 31 parent surveys) and Pediatric Quality of Life Cancer Module 3.0 (PedsQL-Cancer, n = 29 patient and n = 31 parent surveys) were collected from patients and parents. The mean total patient-reported PedsQL score was 73.7, and the parent-reported score was 73.9. There were no significant differences in scores on the PedsQL between patients who underwent resection compared to those who underwent transplantation (p > 0.05 for all comparisons). On the PedsQL-Cancer module, procedural anxiety scores were significantly lower for patients who underwent resection as compared to transplant (M = 33.47 points less, CI [−60.41, −6.53], p-value 0.017). This cross-sectional study demonstrates that quality of life outcomes are overall similar among patients receiving transplants and resections. Patients who received a resection reported worse procedural anxiety.